Pengaruh Service Encounter Terhadap Customer Delight Dan Implikasinya Terhadap Customer Loyalty (Studi Pada Pelanggan Lisung The Dago Boutique Resto di Kota Bandung) - Yulistio Wibowo, - (2019)
ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana gambaran service encounter, customer delight, customer loyalty pada Lisung The Dago Boutique Resto di Kota Bandung, pengaruh service encounter terhadap customer delightdi Lisung The Dago Boutique Resto di Kota Bandung, dan pengaruh customer delight pada customer loyalty di Lisung The Dago Boutique Resto di Kota Bandung. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskripif dan verifikatif. Populasi dalam penelitian ini adalah pelanggan pada Lisung The Dago Boutique Resto di Kota Bandung. Teknik penentuan sampel yang digunakan dalam penelitian ini yaitu teknik non probability sampling dengan teknik accidental sampling, jumlah sampel dalam penelitian ini adalah 128 pelanggan pada Lisung The Dago Boutique Resto di Kota Bandung. Metode analisis yang digunakan dalam penelitian ini adalah analisis Structural Equation Modelling (SEM) dengan metode Partial Least Square (PLS) pada taraf signifikansi sebesar 5%. Program yang digunakan dalam menganalisis data menggunakan SmartPLS. Hasil penelitian menunjukan bahwa secara keseluruhan service encounter, customer delight, dan customer loyalty yang ditunjukan Lisung The Dago Boutique Resto di Kota Bandung termasuk ke dalam kategori baik. Selain itu hasil penelitian menunjukan bahwa service encounter berpengaruh terhadap customer delight. Besarnya pengaruh service encounter dalam memberikan kontribusi pengaurh terhadap customer delight sebesar 71,6%. Sementara customer delight berpengaruh terhadap cusomer loyalty. Besarnya pengaruh customer delight dalam memberikan kontribusi pengaurh terhadap cusomer loyalty sebesar 65,6%. Kata Kunci: Service Encounter, Customer Delight, dan Cusomer Loyalty. The Influence of Service Encounter on Customer Delight and Its Implications on Customer Loyalty (Study of Lisung Customers The Dago Boutique Resto in Bandung City) ABSTRACT This study aims to find out how service encounters, customer delight, customer loyalty to Lisung The Dago Boutique Resto in Bandung, the influence of service encounters on customer delight in Lisung The Dago Boutique Resto in Bandung City, and the influence of customer delight in customer loyalty in Lisung The Dago Boutique Resto in Bandung City. The research method used in this study is descriptive and verification methods. The population in this study were customers at Lisung The Dago Boutique Resto in Bandung City. The sampling technique used in this study is non probability sampling technique with accidental sampling technique, the number of samples in this study is 128 customers at Lisung The Dago Boutique Resto in Bandung City. The analytical method used in this study is the analysis of Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method at a significance level of 5%. The program used in analyzing data using SmartPLS. The results of the study show that the overall service encounter, customer delight, and customer loyalty that Lisung showed The Dago Boutique Resto in Bandung City were included in the good category. In addition, the results of the study show that service encounters affect customer delight. The magnitude of the effect of service encounter in contributing to customer delight is 71.6%. While customer delight affects cusomer loyalty. The amount of influence of customer delight in contributing to the contribution of cusomer loyalty is 65.6%. Keywords: Service Encounter, Customer Delight, and Cusomer Loyalty. The Influence of Service Encounter on Customer Delight and Its Implications on Customer Loyalty (Study of Lisung Customers The Dago Boutique Resto in Bandung City) ABSTRACT This study aims to find out how service encounters, customer delight, customer loyalty to Lisung The Dago Boutique Resto in Bandung, the influence of service encounters on customer delight in Lisung The Dago Boutique Resto in Bandung City, and the influence of customer delight in customer loyalty in Lisung The Dago Boutique Resto in Bandung City. The research method used in this study is descriptive and verification methods. The population in this study were customers at Lisung The Dago Boutique Resto in Bandung City. The sampling technique used in this study is non probability sampling technique with accidental sampling technique, the number of samples in this study is 128 customers at Lisung The Dago Boutique Resto in Bandung City. The analytical method used in this study is the analysis of Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method at a significance level of 5%. The program used in analyzing data using SmartPLS. The results of the study show that the overall service encounter, customer delight, and customer loyalty that Lisung showed The Dago Boutique Resto in Bandung City were included in the good category. In addition, the results of the study show that service encounters affect customer delight. The magnitude of the effect of service encounter in contributing to customer delight is 71.6%. While customer delight affects cusomer loyalty. The amount of influence of customer delight in contributing to the contribution of cusomer loyalty is 65.6%. Keywords: Service Encounter, Customer Delight, and Cusomer Loyalty.